Verstehendes Forschen in der Pandemie und anderen Ausnahmesituationen Praktische und methodologische Erkenntnisse der Rekonstruktiven Sozialen Arbeit - Bartmann, Sylke; Erdmann, Nina; Haefker, Meike; Schörmann, Christin; Dr. Streblow-Poser, Claudia (Rekonstruktive Forschung in der Sozialen Arbeit, 2022)
The COVID-19 pandemic confronts researchers and practitioners of social work with seriously changed conditions. In order to understand such exceptional circumstances, it is necessary to reflect on how different - especially vulnerable - social groups, including service users, professionals and researchers, cope with the state of emergency. Therefore, ways and approaches are analyzed and reflected on the basis of specific projects in order to derive potentials for practice and reconstructive research in social work.